Child and family experiences of a whole-systems approach to physical activity in a multiethnic UK city: a citizen science evaluation protocol. Issue 2 (21st February 2023) - Frazer, Marie; Seims, Amanda; Tatterton, Michael J; Lockyer, Bridget; Bingham, Daniel; Barber, Sally; Daly-Smith, Andy; Hall, Jennifer
Abstract : Introduction: Whole-systems approaches are being adopted to tackle physical inactivity. The mechanisms contributing to changes resulting from whole-systems approaches are not fully understood. The voices of children and families that these approaches are designed for need to be heard to understand what is working, for whom, where and in what context. This paper describes the protocol for the children and families' citizen science evaluation of the Join Us: Move, Play (JU:MP) programme, a whole-systems approach to increasing physical activity in children and young people aged 5–14 years in Bradford, UK. Methods and analysis: The evaluation aims to understand the lived experiences of children and families' relationship with physical activity and participation in the JU:MP programme. The study takes a collaborative and contributory citizen science approach, including focus groups, parent–child dyad interviews and participatory research. Feedback and data will guide changes within this study and the JU:MP programme. We also aim to examine participant experience of citizen science and the suitability of a citizen science approach to evaluate a whole-systems approach. Data will be analysed using framework approach alongside iterative analysis with and by citizen scientists in the collaborative citizen science study. Ethics and dissemination: Ethical approval has been granted by the University of Bradford: study one (E891—focus groups as part of the control trial, E982—parent–child dyad interviews) and study two (E992). Results will be published in peer-reviewed journals and summaries will be provided to the participants, through schools or directly. The citizen scientists will provide input to create further dissemination opportunities.